2009
DOI: 10.1080/02786820903067210
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy Investigation of Particulate Matter from a Dual Fuel Engine

Abstract: The particulate matter (PM) of a dual fuel engine was characterized in size, morphology and fractal geometry by using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Particulate samples were collected from the diluted exhaust of the engine operated on diesel fuel, natural gas (NG) and synthetic biogas. The engine operating condition was kept the same to compare the results between diesel and dual fuel PM. SEM images yielded agglomerate number, size distributions and a shape descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
3
17
2
Order By: Relevance
“…5a). This is in general agreement with results previously reported in the literature for aerosols emitted by diesel engines (Park et al , 2004; Mathis et al , 2005; Lapuerta et al , 2007; Mustafi and Raine, 2009). The general morphology of the EOut aerosols was not discernibly affected by the additives and engine operating conditions.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…5a). This is in general agreement with results previously reported in the literature for aerosols emitted by diesel engines (Park et al , 2004; Mathis et al , 2005; Lapuerta et al , 2007; Mustafi and Raine, 2009). The general morphology of the EOut aerosols was not discernibly affected by the additives and engine operating conditions.…”
Section: Resultssupporting
confidence: 93%
“…(2006) [25 nm], Neer and Koylu (2006) [28–34 nm], Lapuerta et al (2007) [18–30 nm], and Mustafi and Raine (2009) [25–30 nm]. In all cases, the mean size and number of primary particles were equal or greater for I100 than for I50 conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that both effective density (at each mobility size) and primary particles size is similar for the three cases suggests also that the morphology at a given mobility diameter is similar between the three cases. Lee et al (2002), Mustafi andRaine (2009), andPark et al (2004) investigated the structural properties of diesel soot and mentioned that the mean primary particle diameter ranged from (2007) and Burtscher (2005) showed that the engine design, operating conditions, and lube oil influence the properties of PM emissions. In general, a somewhat larger primary particle size range was found from different diesel engines, compared to diffusion flame generators.…”
Section: Particle Composition Effective Density Andmentioning
confidence: 99%
“…The number of primary particles per agglomerate, N, was calculated using Equation 2, where K a represents an empirical constant and α represents an empirical coefficient (Oh and Sorensen 1997; Mustafi and Raine 2009). N=Kα(AcAp)α…”
Section: Resultsmentioning
confidence: 99%
“…For this study, values of 1.35 and 1.1 were selected for K a and α, respectively, based on literature values for diesel engine operation at conditions other than high fueling/heavy load and considering the overlap of the primary particle spheres in the typical agglomerate (Oh and Sorensen 1997; Mustafi and Raine 2009). After N was determined per Equation 2, the fractal dimension, D fL , was calculated by solving for the slope of the ln (N) versus ln (L max /d p ) plot (Mustafi and Raine 2009).…”
Section: Resultsmentioning
confidence: 99%